The Gulf Conflict - Fred Hill (International Institute of Islamic Thought, 1997)
Writers have compared the media frenzy of the Gulf War to the coverage of a football game. Critics noted the pep rally atmosphere created by journalists (Charles Osgood's description of US bombing as a "marvel"; Dan Rather's "Congratulations on a job wonderfully done."). A Chicago Tribune cartoon portrayed Saudi and Kuwaiti emirs in luxury boxes awaiting the war, heckling Bush to “Throw the bomb!” Perhaps it was that pause in the second week of the bombing, allowing most US soldiers to watch the Super Bowl, but Americans did seem to confuse the war with a sporting event. Both features perceived good guys and bad guys, satisfying but guilt-free violence, little sympathy for the casualties . . . and plenty of cheerleaders. Books about the Gulf War extend this comparison to sports coverage. After the big game, our fist wave of analysts report from postgame interviews. These are generally shallow and simplistic, breathless with elation and self-glory. Comparable books on the Gulf War, including biographies of Schwarzkopf, Powell, and Bush, now cram the discount tables at the large booksellers. In sports, the second wave of analysts, back in the studio, offer somewhat meatier explanations and more subtle rationalizations for the events just reported. Their emotions are thinly concealed in a semblance of objectivity ...